Implementation Of BPK Corporate University Policy At The State Financial Audit Education And Training Agency Of BPK RI - Anita Riknawati; Dahyar Daraba; Dyah Poespita Ernawati (INFOKUM, 2025)
BPK RI Establishes BPK Corporate University in 2021 as a strategy used to achieve BPK's vision and mission, by realizing a link and match between learning, knowledge management, and application of values ​​with BPK's performance targets. Therefore, the author is interested in taking the title "Implementation of BPK Corporate University Policy at BPK RI's PKN Education and Training Center". This study aims to describe and analyze the implementation of BPK Corporate University policy, inhibiting and supporting factors, and efforts to overcome these obstacles. This research method uses a qualitative research method with a descriptive approach. The data collection techniques used are interviews, observations, and documentation. The informants in this study were 19 (nineteen) people who were determined using purposive sampling and snowball techniques. The data analysis technique used is triangulation. Based on the results of the research and discussion, it can be concluded that the implementation of the BPK Corporate University policy at BPK RI's PKN Education and Training Center is still not running well and needs to be optimized, this can be seen in several aspects, namely communication, resources, disposition, and bureaucratic structure. The things that support the implementation of the BPK Corporate University policy are competent human resources, ease of coordination, the formation of a learning committee, and the existence of a digital learning system platform, while the things that hinder are the lack of human resources at the PKN Education and Training Center, the lack of support and role of the learning committee, the lack of employee learning motivation, the unavailability of BPK Corporate University Standard Operating Procedures (SOP), the suboptimal management of the Knowledge Management System (KMS) and Integrated Learning Model (ILM). The efforts made by the PKN Education and Training Center include proposing additional and improving the quality of human resources, increasing socialization, designing various learning methods and media, and improving coordination